+0  
 
0
232
1
avatar+409 

Simplify: (2^(2+4)-2(2^n))/(2(2^(n+3)). Express your answer as a common fraction.

 Jan 17, 2019
edited by APatel  Jan 17, 2019
 #1
avatar+111326 
+2

 (2^(2+4)-2(2^n))/(2(2^(n+3)).  =

 

[ 2^6  - 2(2^n ] / [ 2 * 2^(n + 3) ]  =

 

[ 2^6 - 2^(n + 1) ] / [ 2^(n + 4) ]  =

 

[ 64 - 2^(n + 1) ] / [2 ^(n + 4)  ]  =

 

[ 2 * 2^5 - 2 * 2^n ] / [ 2* 2^(n + 3) ] =

 

[ 2^5 - 2^n ] / [ 2^(n + 3) ]  =

 

[32 - 2^n ] / [ 8 * 2^n ]   

 

This is all we can do

 

 

cool cool cool

 Jan 17, 2019

39 Online Users

avatar
avatar
avatar
avatar